Case series of Dissociative Dysphonia at Interface of Paediatrics, ENT and Psychiatry Departments - Dias, Edwin; Mithun, S. (New Horizons in Medicine and Medical Research Vol. 11, 2022)
Two case series of Dissociative Dysphonias at the interface of Departments of Paediatrics, ENT and Psychiatry are being described here. One case is of dysphonia plica ventricularis and emotional dysregulation who presented to the Paediatrics department. And another case is of dissociative dysphonia with delusional disorder presenting to the ENT department. Dysphonia plica ventricularis (DPV) is a type of functional dysphonia (FD) which can be caused by several reasons. DPV- emotional type is seen secondary to emotional crisis which is equivalent to psychogenic/dissociative dysphonia. Here we describe a case of DPV secondary to emotional dysregulation with an underlying emotionally unstable personality disorder. Crisis intervention and emphasis on regular compliance to treatment has been discussed. Dissociative dysphonia is less commonly seen in general population. Previous literature has focused on interplay of dysphonia mainly in schizophrenia or schizoaffective disorders. Here we discuss a unique case of delusional disorder with dissociative dysphonia. The challenges in the evaluation and management are discussed.